Unemployment and Recruitment with Heterogeneous Labor - Hosios, Arthur J. (Journal of Labor Economics, 1985)
This paper describes the equilibrium wage distribution and unemployment rate when firms recruit (search for) employees. A model in which firms' inability to distinguish workers who refuse job offers increases their expected recruiting costs, is contrasted with one in which indistinguishable low-productivity workers decrease firms' expected gains from hiring. In both, work force heterogeneity enhances search uncertainty, firms recruit less intensively than otherwise, and so the equilibrium unemployment rate rises. Heterogeneity reflects searchers' incomplete knowledge of desirable trading partners' locations and will likely be a confounding influence and source of unemployment in large economies with imperfectly observable sector-specific shocks.